About the environment - Calderón-Rehecho, Andoni (Anuario ThinkEPI, 2023)
A reflexion on the increasing technological dependence on hardware and software that serve to monitor us and persuade us is carried out. This dependence is accentuated by the expansion of artificial intelligence (AI) and its fragility in the face of cybersecurity problems (connecting business and warfare), which is one of the keys to the future.
Keywords: AI; Attention economy; Automation bias; ChatGPT; Cybersecurity; Persuasive technology; Surveillance capitalism; The age of attention